Association between Weight-Adjusted Waist Index and Depression in NAFLD: the modulating roles of sex and BMI - Jingwen Zhang; Yan Wang; Sunkui Ke; Tianyu Xie; Lijun Liu; Xiaoyu Fu; Chenhao Wang; Xiao Huang (BMC Psychiatry)
Abstract Background The Weight-Adjusted Waist Index (WWI) is a novel indicator of obesity that accurately reflects body composition. However, the association between WWI and depression in patients with non-alcoholic fatty liver disease (NAFLD) remains unclear. This study aims to explore this relationship through a nationally representative cross-sectional analysis. Methods This study included adult participants diagnosed with NAFLD from NHANES 2017–2020. WWI was calculated as the waist circumference (cm) divided by the square root of body weight (kg). NAFLD diagnosis relied on vibration-controlled transient elastography (VCTE) with a controlled attenuation parameter (CAP) exceeding 248 dB/m to indicate hepatic steatosis. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9), with scores ≥ 10 indicating the presence of major depression. Results After adjusting for all covariates, a significant positive association was found between WWI and depression in NAFLD (OR = 1.725, 95% CI: 1.442–2.063, p < 0.00001), with a dose-response relationship indicated by restricted cubic spline analysis. The association was stronger in men and lean/normal weight NAFLD patients. Adjusting further for BMI did not alter these findings (OR = 1.643, 95% CI: 1.357–1.989, p < 0.00001). BMI’s association with depression was negated after adjusting for WWI. Conclusions WWI had a positive association with depression in NAFLD, independent of BMI. This association was more pronounced in men and lean/normal weight NAFLD. These findings suggest that WWI may be a novel indicator of depression in NAFLD and potentially valuable in depression prevention.